Pemanfaatan Limbah Agroindustri sebagai Bahan Baku Produksi Bioethanol Fuel Grade untuk Substitusi Bahan Bakar Fosil - Anang Baharuddin Sahaq; Salwa Asyifa; Aulia Firda Alfiana (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The utilization of agro-industrial waste as a feedstock for fuel-grade bioethanol offers a strategic opportunity to reduce dependence on fossil fuels and support the transition toward renewable energy. This study provides a systematic review of the potential of various Indonesian agro-industrial wastes, including lignocellulosic and non-lignocellulosic materials, along with the variation in ethanol yields produced through pretreatment, hydrolysis, fermentation, and purification processes. The analysis shows that feedstock characteristics, pretreatment efficiency, and microbial fermentation performance are key determinants of ethanol yield. A major challenge lies in the purification stage, as ethanol obtained from conventional distillation does not meet the fuel-grade requirement of ≥99.5% v/v. Several dehydration technologies—such as azeotropic distillation, extractive distillation, molecular sieves, membrane pervaporation, and PSA—can achieve high purity with distinct operational advantages. This review highlights the importance of integrating suitable purification methods and optimizing the conversion process to produce fuel-grade bioethanol that is technically and economically feasible. Overall, agro-industrial waste demonstrates significant potential to support national energy security and sustainability